Tantangan dan peluang pengembangan asuransi syariah di era modern: Tinjauan studi literatur - Auril, Sheryn Alivia (Maliki Interdisciplinary Journal, 2026)
It has grown along with increasing public awareness of sharia-based finance. However, this sector still faces various challenges, ranging from low public literacy to limited product innovation and digital technology. This study aims to review the literature related to the challenges and opportunities for developing sharia insurance in Indonesia using a literature study approach. The results of the study show that the main opportunities lie in increasing market penetration, regulatory support from the Financial Services Authority (OJK), and digital transformation that expands the reach of services. The main challenges include a lack of professional human resources, minimal public understanding of the concept of takaful, and competition with conventional insurance. This study emphasizes the importance of a synergistic strategy between regulation, innovation, and public education to strengthen the sustainability of the Islamic insurance industry in the modern era.